Impact of Diabetes Mellitus on the Aortic Wall Changes as Atherosclerosis Progresses: Aortic Dilatation and Calcification - Iwakawa, Naoki (J Atheroscler Thromb, 2020)
Aim: An inverse association between diabetes mellitus (DM) and aortic dilatation has recently been reported. However, little is known about the association between DM and the progression of aortic dilatation/calcification as atherosclerosis progresses. Methods: We identified 216 patients who had undergone percutaneous coronary intervention (PCI) and abdominal computed tomography (CT) during the PCI and follow-up phases. The patients were classified into two groups: those with DM (DM+ group; n = 107) and those without DM (DM− group; n = 109). The infrarenal aortic diameter and aortic calcification index (ACI) were measured, and annual changes were calculated using measurement results obtained during the PCI and follow-up phases. Results: Infrarenal aortic diameters were significantly shorter in the DM+ group than in the DM− group during the PCI phase, and no significant ACI differences were observed between the DM+ and DM− groups. The median duration between the PCI and follow-up phase CT was 3.0 years. The growth rate of the infrarenal aortic dilatation from the PCI phase in the DM+ group was similar to that in the DM− group. Annual ACI changes were significantly larger in the DM+ group than in the DM− group. Multivariate logistic regression analysis indicated that the prevalence of DM was an independent predictor of rapid aortic calcification progression (odds ratio: 2.51; 95% confidence interval: 1.23–5.14; p = 0.01). Conclusion: Our findings suggest that DM negatively affects aortic dilatation during an earlier phase of atherosclerosis progression and positively affects the progression of aortic calcification in a later phase.